Exploring the community pharmacist's role in palliative care: Focusing on the person not just the prescription - O'Connor, Moira; Fisher, Colleen; French, Lauren; Halkett, Georgia; Jiwa, Moyez; Hughes, Jeffery (Elsevier Ireland Ltd, 2011)
Objective: Changes in health care provision have led to an emphasis on providing end of life care within the home. Community pharmacists are well positioned to provide services to community-based palliative care patients and carers. Methods: A multiple qualitative case study design was adopted. A total of 16 focus groups and 19 interviews with pharmacists, nurses, general practitioners and carers were undertaken across metropolitan and regional settings in Western Australia, New South Wales, Queensland and Victoria. Data were analysed thematically using a framework that allowed similarities and differences across stakeholder groups and locations to be examined and compared. Results: Three main themes emerged: effective communication; challenges to effective communication; and: towards best practice, which comprised two themes: community pharmacists’ skills and community pharmacists’ needs. Discussion: A key component of the provision of palliative care was having effective communication skills. Although community pharmacists saw an opportunity to provide interpersonal support, they suggested that they would need to develop more effective communication skills to fulfil this role. Conclusion: There is clear need for continuing professional development in this area – particularly in communicating effectively and managing strong emotions. Practice implications: Community pharmacists are willing to support palliative care patients and carers but need education, support and resources.